PENGARUH FI’LIYAH, QAULIYAH, DAN BATHINIYAH SHALAT TERHADAP PERILAKU REMAJA MELALUI KEKHUSYUKAN SHALAT - Siregar, Nur Asyiah; Harahap, Hotni Sari (HIBRUL ULAMA, 2024)
This study investigates the impact of fi’liyah (actions), qauliyah (utterances), and bathiniyah (intention) of shalat (prayer) on adolescent behavior, moderated by the concentration (khusyuk) during shalat. Conducted at Madrasah Tsanawiyah Uli Arga Marindal, the research additionally addresses moral issues observed in Indonesian youth, who are increasingly involved in criminal activities. The motivation behind this study lies in the need for a more profound religious understanding and practice among adolescents, fostering positive behavior changes. Employing a quantitative descriptive approach, data were collected through questionnaires and analyzed using the SmartPLS 4. 1. 0. 3 software to assess the relationships between variables. The findings reveal that while fi’liyah does not significantly impact khusyuk, both qauliyah and bathiniyah positively influence it. Furthermore, a significant correlation was established indicating that fi’liyah, qauliyah, and bathiniyah collectively enhance adolescent behavior through increased khusyuk. This emphasizes the critical importance of these aspects of shalat in shaping youthful conduct and highlights the potential for integrating religious practices into moral development programs for teenagers.